2014
DOI: 10.1007/s10815-014-0345-6
|View full text |Cite
|
Sign up to set email alerts
|

Follicular fluid Aβ40 concentrations may be associated with ongoing pregnancy following in vitro fertilization

Abstract: Aβ40 levels in follicle fluid may be associated with ongoing pregnancy and the moderate expression level of Aβ40 is important for oocytes and embryos development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…For example, results of a 2014 study by Gao B found that an ABCB1 blocker inhibited paclitaxel efflux from all ovarian cancer cell lines regardless of ABCB1 expression level, thus indicating that an ABCB1 transporter plays a key role in paclitaxel resistance of ovarian cancer cells. In another study (Gao et al, 2014), Duan et al (2014) found that APP negatively regulated APP precursor protein hydrolysate. A activity during an in vitro fertilization study of plasma amyloid-β 40 regulation of ovarian cancer development (Duan et al, 2014).…”
Section: Molecular Docking Analysismentioning
confidence: 96%
See 1 more Smart Citation
“…For example, results of a 2014 study by Gao B found that an ABCB1 blocker inhibited paclitaxel efflux from all ovarian cancer cell lines regardless of ABCB1 expression level, thus indicating that an ABCB1 transporter plays a key role in paclitaxel resistance of ovarian cancer cells. In another study (Gao et al, 2014), Duan et al (2014) found that APP negatively regulated APP precursor protein hydrolysate. A activity during an in vitro fertilization study of plasma amyloid-β 40 regulation of ovarian cancer development (Duan et al, 2014).…”
Section: Molecular Docking Analysismentioning
confidence: 96%
“…In another study (Gao et al, 2014), Duan et al (2014) found that APP negatively regulated APP precursor protein hydrolysate. A activity during an in vitro fertilization study of plasma amyloid-β 40 regulation of ovarian cancer development (Duan et al, 2014). More recently, in 2020, Chulpanova et al confirmed that amniotic fluid-derived mesenchymal stem cells (MSCs) expressing IL-2 could induce ovarian cancer cell apoptosis in vivo (Chulpanova et al, 2020), while the results of another study revealed that high expression of MAPT was linked to poor ovarian cancer prognosis, thus indicating that inhibition of MAPT expression could improve ovarian cancer prognosis (Schroeder et al, 2019).…”
Section: Molecular Docking Analysismentioning
confidence: 96%